Effect of Dormant ‘MidIron’ Bermudagrass Colorant Applications on Clothing Blemishing - J. Hoyle; Daniele L. McFadden (Kansas Agricultural Experiment Station Research Reports, 2017)
Minimal research exists on potential clothing blemishing when athletes contact turfgrass applied with colorants. Field trials were initiated February 16, 2017, and conducted to test the effect of turfgrass colorant applications on clothing blemishing if an athlete is to come in contact with the playing surface. Turfgrass colorants will adhere to turfgrass leaf blades and do not blemish clothing. However, tested turfgrass pigments did result in significant blemishing of clothing.
Keywords: turfgrass colorants; clothing blemishing